Taylor-Couette Column for Emulsion Liquid Membrane System: Characterisation Study (Universitas Negeri Semarang, 2019)
Study on the application of Taylor-Couette column for emulsion liquid membrane system has been done. To optimise extraction process under TCC, a research to investigate effect of viscosity and cylinders rotation is of important. Fluid viscosity was examined by varying volume ratio of kerosene to water. TCC was characterised to determine flow regimes, shear stress, and energy loss distribution. Volume ratio of oil to water was varied at 1:1, 1:3, 1:5, and 1:6 while inner and outer cylinders speed were maintained constant at 300 and 200 rpm, respectively. Investigation on the effect of volume ratio of oil to water towards flow regime ended to same flow regime of Featureless Turbulent. There was degradation of wall shear stress from 8.57x10-2 Pa to 7.42x10-2 Pa.